2013
DOI: 10.1007/s11434-013-5942-8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical estimations of atmospheric duct over the South China Sea and the tropical eastern Indian Ocean

Abstract: In 2010-2012 spring, atmospheric duct observation experiments were performed throughout three open cruises over the South China Sea and the Tropical Eastern Indian Ocean. The data used for ducting analysis were measured by high resolution balloon-borne GPS radiosondes. Through data quality control and diagnostic analysis, the probability of ducting occurrence and characteristic quantities of the three typical ducts were given. The total percentage occurrence of evaporation duct, surface-based duct and elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…GPS sounding data from the SCSIO open cruises were used to study the characteristics of atmospheric ducts over the SCS. The results showed that the occurrence probabilities of evaporation ducts, surface-based ducts, and elevated ducts were 75.3%, 5%, and 43.7%, respectively, and the mean evaporation duct height was 15.3 m (Zhao et al 2013).…”
Section: Sc I E Nti F Ic Applic Atio N Smentioning
confidence: 99%
“…GPS sounding data from the SCSIO open cruises were used to study the characteristics of atmospheric ducts over the SCS. The results showed that the occurrence probabilities of evaporation ducts, surface-based ducts, and elevated ducts were 75.3%, 5%, and 43.7%, respectively, and the mean evaporation duct height was 15.3 m (Zhao et al 2013).…”
Section: Sc I E Nti F Ic Applic Atio N Smentioning
confidence: 99%
“…Based on highresolution Global Position Systerm (GPS) radiosonde data, they found that summer monsoons exerted important infl uence on lower-atmospheric ducts over the SCS. Zhao et al (2013) estimated the characteristics of ducts in the tropics in spring. Despite improvements in duct climatology, the duct characteristics for the SCS are still not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…This clutter can be described as a function of propagation loss from the radar to the range cell, which in turn depends on the refractivity profile in the troposphere (Kraut et al 2004). Compared with conventional in situ refractivity measurements, such as radiosondes, rocketsondes, and microwave refractometers (Babin and Rowland 1992;von Engeln and Teixeira 2004;Mentes and Kaymaz 2007;Ali et al 2012;Zhao et al 2013), RFC has the advantages of employing the radar itself as the remote sensing device and can provide temporal and spatial tracking of the refractive information in a dynamically changing environment (Wang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In general, the statistics of these errors are unknown. To characterize the profile more accurately, the adjoint method has been demonstrated to be a good choice (Zhao and Huang 2012). In Zhao and Huang (2012), numerical simulations of an evaporation duct case were considered, and the clutter observations were assumed to be no noise pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation